Beyond the Classroom Walls: Indonesian EFL Students’ Self-Regulated Learning Experiences in a Flipped Listening Classroom - Destina Kasriyati; Ribut Wahyu Eriyanti; Diah Karmiyati; Nurfaisal Nurfaisal; Puput Arfiandhani; Syahdan Syahdan (Universitas Muhammadiyah Mataram, 2026)
The rapid advancement of Information and Communication Technology (ICT) has transformed higher education, positioning the Flipped Classroom Model (FCM) as a strategic pedagogical innovation for student-centered learning. This study addresses a significant gap in the literature regarding how students independently regulate their learning within less structured environments, specifically focusing on the